A Case Study of Corporate Facilitated Community Based Tourism Development at Ide Sorowako Beach - Masriana Masriana; Masour Shqiarat; Nuttapong Jotikasthira (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to analyze the mechanisms of corporate-community collaboration in CBT development. It specifically seeks to answer: "How does the partnership between PT. Vale and the local community shape the implementation and outcomes of CBT at Ide Sorowako Beach?" The research also identifies the key supporting and inhibiting factors within this tripartite governance model. Methodology: Employing a qualitative descriptive design, this study is grounded in a phenomenological approach to understand stakeholder experiences and a collaborative governance theoretical lens to analyze partnership structures. Data were collected via in-depth interviews, participatory observation, and document analysis involving government officials, PT. Vale management, and local community members (n= [isi jumlah informan]). Data were analyzed thematically using an interactive model, with triangulation ensuring validity and credibility. Main Findings: The analysis reveals that PT. Vale’s management adopts a participatory approach, actively involving the community in operational decision-making, which has led to direct economic benefits. However, community participation remains limited to the operational level, with strategic planning still dominated by corporate agendas. Key supporting factors are the site's natural capital and corporate resource provision. Novelty/Originality of this study: This study contributes to the CBT literature by providing an empirical analysis of a hybrid governance model where corporate CSR initiatives directly interface with community-driven tourism. It moves beyond generic CSR descriptions to dissect the mechanics and power dynamics of such partnerships. T